Using Animation, Symbolism and Discovery to Convey a Global Social Issue - Hodgkinson, Gray (2017)
Guided discovery is a key principle of constructivist learning. (Mayer 2004). The act of discovery creates an irrefutable physiological experience in the learner; an experience that reinforces an expectation for more discovery, creating a positive cycle of discover, learn, discover, and so on. (Hodgkinson 2008). This paper looks at story-telling using symbolism to generate the sense of discovery in the viewer. Using an animated movie to explore the global social issue of immigration, a range of techniques including metaphor and symbolism are used to generate discovery in the viewer, turning the viewer from a passive participant to an active participant. In doing so, this paper seeks to demonstrate that any potentially passive situation can be turned around into a discovery-filled cognitively engaging activity.